Pengaruh Media Bola Spons Terhadap Kemampuan Passing Bawah Bola Voli Siswa Sekolah Dasar - Tuba, Moch. Dzakyyut; Cahyani, Olivia Dwi; Priadana, Benny Widya (Universitas Hamzanwadi, 2026)
The underhand passing skills of elementary school students are still relatively low, partly due to the use of learning media that are not suited to the motor and psychological characteristics of the students. This study aims to examine the effect of using sponge balls on improving underhand passing skills in volleyball. The study used a pre-experimental method with a one-group pretest-posttest design, involving 20 fifth and sixth grade students from SDN Wadang III as samples selected through purposive sampling. The intervention was carried out through structured training using sponge balls in several learning sessions. Data were collected through an underhand passing skill test that had been tested for content validity and reliability (test-retest r = 0.819), then analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired sample t-test. The results showed a significant improvement in students' underhand passing skills, as indicated by an increase in the average score from 3.90 to 8.05, a shift in the distribution of skill categories toward better performance, and a significant t-test result (p < 0.001). The study concluded that sponge balls are an effective medium for improving elementary school students' underhand passing skills in volleyball. Its lightweight, soft, safe, and easy-to-control nature reduces fear, increases confidence, and facilitates more optimal learning of basic techniques.